Training of trainers report - Mhlanga, Blessing; Setimela, Peter; Chiduwa, Mazvita Sheila; Thierfelder, Christian (CIMMYT, 2025)
As part of CIMMYT’s contribution to the Scaling for Impact (S4I) Initiative, a Training of Trainers (ToT) was conducted from 23–27 October 2025 to strengthen partner capacity for the scaling of bundled soil, water, mechanization, and seed system innovations. The training was delivered in conjunction with the Water & Soil Accelerator (WASA), which served as a primary implementation and learning platform for testing and refining scalable solutions. The training targeted technical, research, and extension staff from Conservation Farming Unit (CFU), Total LandCare (TLC), Foundation for Farming (FoF), and collaborating institutions, including the African Fertilizer and Agribusiness Partnership (AFAP), Pelum, and the Ministry of Agriculture in Zambia and Malawi. The overall objective was to strengthen system readiness for scaling by equipping partners with practical skills to implement, adapt, and monitor standardized innovation bundles, including: i. Conservation Agriculture (CA) practices; ii. Small-scale mechanization using basin diggers; iii. Legume seed multiplication and quality assurance; and iv. Robust agronomic and implementation data systems. Three training sessions were conducted: i. Session 1: Chongwe District, Central Zambia – CFU (16 participants; 38% women; 44% youth); ii. Session 2: Msekera Research Station, Eastern Zambia – TLC & FoF (7 participants; 29% women; 43% youth); iii. Session 3: Mchinji District, Malawi – TLC, AFAP, Pelum, Ministry of Agriculture (22 participants; 27% women; 22% youth). Across all sessions, 45 participants (31% women; 36% youth) were trained through a combination of classroom instruction, hands-on field implementation, and peer learning. While WASA protocols and demonstration sites were used as the operational backbone, the training explicitly focused on scaling functions central to S4I, including partner capacity, data systems, implementation fidelity, contextual adaptation, and coordination across institutions. The training contributes directly to CGIAR Impact Areas, particularly: i. Climate adaptation and mitigation (improved soil water management and resilience); ii. Environmental health and biodiversity (soil cover, residue retention, diversified systems); iii. Poverty reduction, livelihoods, and jobs (mechanization service opportunities); and iv. Gender equality, youth, and social inclusion (deliberate inclusion and leadership pathways).